2011
DOI: 10.1002/humu.21595
|View full text |Cite
|
Sign up to set email alerts
|

dbHCCvar: A comprehensive database of human genetic variations in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma is a common cancer with a high mortality rate. The complete pathogenesis of hepatocellular carcinoma is not completely understood, and highly efficient therapy is still unavailable. In the past several decades, various genetic variations such as mutations and polymorphisms have been reported to be associated with hepatocellular carcinoma risk, progression, survival, and recurrence. However, to our knowledge, these genetic variations have not been comprehensively and systematically comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
(31 reference statements)
0
12
0
1
Order By: Relevance
“…HCC.Net, which has compiled a network with thousands of HCC-related genes identified in different types and stages of HCC, contains 2,131 HCC-related genes [14]. dbHCCvar is an online database which contains 636 human genetic variations and 195 human genes which have been statistically tested to be associated with HCC [15]. EHCO is derived from thirteen gene sets related to HCC and gives 3833 HCC-significant genes [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HCC.Net, which has compiled a network with thousands of HCC-related genes identified in different types and stages of HCC, contains 2,131 HCC-related genes [14]. dbHCCvar is an online database which contains 636 human genetic variations and 195 human genes which have been statistically tested to be associated with HCC [15]. EHCO is derived from thirteen gene sets related to HCC and gives 3833 HCC-significant genes [16].…”
Section: Methodsmentioning
confidence: 99%
“…Our study group has recently developed two systems biology-based classifiers for early diagnosis of HCC and prostate cancer (PCa), respectively, by combining differential gene and protein expression and topological characteristics of human protein interaction networks, and also demonstrated that these classifiers may efficiently enhance the diagnostic performance for HCC and PCa [11,12]. On this basis, in the current study, we intend to collect full-scale HCC related data including HCC significant genes and proteins which were differentially expressed or had genetic variations in HCC tissues relative to their corresponding normal tissues from five existing HCC related databases (OncoDB.HCC [13], HCC.net [14], dbHCCvar [15], EHCO [16] and Liverome [17]). In order to investigate the functional relationships between these significant molecules, we constructed the protein-protein interaction network and analyzed the topological features of nodes to screen novel markers for HCC.…”
Section: Introductionmentioning
confidence: 99%
“…HCC.Net, which has compiled a network with thousands of HCC-related genes identified in different types and stages of HCC, contains 2,131 HCC-related genes25. dbHCCvar is an online database which contains 636 human genetic variations and 195 human genes which have been statistically tested to be associated with HCC26. EHCO is derived from thirteen gene sets related to HCC and gives 3833 HCC-significant genes27.…”
Section: Methodsmentioning
confidence: 99%
“…The present review will summarize the influence of this inherited background on the risk of HCC with the constant will to illustrate both the limitations and the progress made in this field. For a more exhaustive overview, free online databases providing comprehensively and systematically compiled genetic associations have been recently established [58].…”
Section: Genetic Predisposition and Hccmentioning
confidence: 99%